Identification, Characterization, and Antioxidant Potential of Bifidobacterium longum subsp. longum Strains Isolated From Feces of Healthy Infants - Zhao, Li; Wang, Song; Dong, Jiahuan; Shi, Jialu; Guan, Jiaqi; Liu, Deyu; Liu, Fei; Li, Bailiang; Huo, Guicheng (Frontiers in Microbiology, 2021)
Increasing evidence has indicated that oxidative stress is associated with the health of infants. Bifidobacterium especially Bifidobacterium longum subspecies longum (B. longum subsp. longum) strains are abundant in the gut microbiota of infants, which may have the potential to ameliorate oxidative damage. Thus, the aim of this study was to isolate and screen B. longum subsp. longum strains with probiotic characters and antioxidant property as infants’ dietary supplements. In this study, 24 B. longum subsp. longum strains were isolated from 15 healthy infants identified via 16S rRNA and heat shock protein 60 (hsp60) sequences. B. longum subsp. longum B13, F2, K4, K5, K10, K13 and K15 were selected with the high ability of adhesion according to the assays of autoaggregation, hydrophobicity, and adhesion property to HT-29 cells. Among these 7 strains, B. longum subsp. longum F2, K5, K10 and K15 were selected according to the high tolerance of gastrointestinal tract conditions compared to B. animalis subsp. lactis BB12. Among these 4 strains, B. longum subsp. longum K5 was susceptible to commonly antibiotics and showed highest intestinal epithelial cell proliferation of CCD 841 CoN. Additionally, B. longum subsp. longum K5 showed a strong capacity of antioxidant, and the supernatant of the strains exhibited better activity of reducing power, hydroxyl radical scavenging, and DPPH radical scavenging than that of the intact cells and cell-free extracts. The findings indicated that B. longum subsp. longum K5 could be used as a candidate of probiotics applied in the various productions with potential of antioxidant as probiotics for infants.